Efficacy of nivolumab as second-line treatment for elderly patients with metastatic malign melanoma (Annals of Medical Research, 2023)
Aim:  This study aimed to analyse the clinical characteristics, effectiveness and safety of nivolumab monotherapy in patients aged≥ 65 years with metastatic melanoma.Materials and Methods: This study involved patients aged ≥65 years who were diagnosed with metastatic cutaneous or mucosal melanoma. Patients with BRAF wild type, ECOG performance status 0-1, and who had previously received one line of chemotherapy were included, irrespective of PD-L1 expression. The study analyzed PFS, OS, and adverse event profiles.Results: Twenty-one patients, with a median age of 70, were analysed in the study. The median PFS for nivolumab as second-line therapy in elderly patients was 3.5 months (95% CI, 1.5 to 5.6 months), while the median OS was 14.5 months (95% CI, 10.3 to 18.6 months). The most common grade 1-2 adverse events were anemia (66.7%) and serum creatinine increase (23.8%). Additionally, the rate of grade 3-4 adverse events due to all causes was 28.6%. There was no grade 5 adverse event.Conclusion: Nivolumab is effective and safe as second-line therapy in patients aged ≥65 years with metastatic melanoma. It is a tolerable and effective treatment choice for elderly patients who cannot received nivolumab in first line therapy.
Keywords: Nivolumab; Elderly patients; Malign melanoma; Anti pd-1